Exploring Teachers’ Experiences in Integrating SAMR-Based Adaptive Technology in Primary English Reading–Writing Instruction - Syukran, Rahmat; Adriansyah, Adriansyah; Alimir, Immatul Jannah; Syafitri, Widya; Sesmiarni, Zulfani; Bayu, Eka Pasca Surya (El-Rusyd, 2025)
The implementation of educational technology often remains at the level of substituting conventional media, rather than reflecting a deeper understanding of adaptive technology and its potential to transform learning processes. This qualitative descriptive study employed an exploratory approach to investigate English teachers’ experiences and perceptions regarding the integration of SAMR-based adaptive technology in integrated reading–writing instruction at the primary level. Data were collected through semi-structured interviews, classroom observations, and document analysis involving primary school English teachers and were analyzed using the interactive model proposed by Miles, Huberman, and Saldana. The findings reveal that technology integration predominantly occurs at the Substitution (S) and Augmentation (A) levels of the SAMR framework, with limited evidence of modification or redefinition in instructional practices. This indicates that the transformative potential of SAMR-based adaptive technology has not yet been optimally realized in integrated primary literacy instruction. Strengthening teachers’ digital pedagogical competencies and reconceptualizing technology integration as a means of restructuring learning processes are therefore essential to support more meaningful, contextually relevant literacy learning aligned with 21st-century educational demands.